Markets on trial the economic sociology of the U.S. financial crisis - Lounsbury, Michael; Hirsch, Paul Morris (Emerald, 2010)
Since the mid-20th century, organizational theorists have increasingly distanced themselves from the study of core societal power centers and important policy issues of the day. This has been driven by a shift away from the study of organizations, politics, and society and towards a more narrow focus on instrumental exchange and performance. As a result, our field has become increasingly impotent as a critical voice and contributor to policy. For a contemporary example, witness our inability as a field to make sense of the recent U.S. mortgage meltdown and concomitant global financial crisis. It is not that economic and organizational sociologists have nothing to say. The problem is that while we have a great deal of knowledge about finance, the economy, entrepreneurship and corporations, we fail to address how the knowledge in our field can be used to contribute to important policy issues of the day. This double-volume brings together some of the very top scholars in the world in economic and organizational sociology to address the recent global financial crisis debates and struggles around how to organize economies and societies around the world.
Description based on print version record.
Keywords: Economics -- Sociological aspects.; Global Financial Crisis, 2008-2009.; United States -- Economic conditions -- 2001-2009.; elektronické knihy; electronic books